2021
DOI: 10.33594/000000396
|View full text |Cite
|
Sign up to set email alerts
|

Uremia and Inadequate Oxygen Supply Induce Eryptosis and Intracellular Hypoxia in Red Blood Cells

Abstract: BACKGROUND/AIMS: Chronic kidney disease is frequently accompanied by anemia, hypoxemia, and hypoxia. It has become clear that the impaired erythropoietin production and altered iron homeostasis are not the sole causes of renal anemia. Eryptosis is a process of red blood cells (RBC) death, like apoptosis of nucleated cells, characterized by Ca2+ influx and phosphatidylserine (PS) exposure to the outer RBC membrane leaflet. Eryptosis can be induced by uremic toxins and occurs before senescence, thus shortening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…If we cannot get timely and effective counseling and nursing intervention, the continuous bad psychological state is easy to develop into anxiety disorder and depression, which will have a negative impact on the quality of life of patients. Studies have shown that the incidence of depressive symptoms in uremic patients is 68.8%, which is basically the same as 68.0% found abroad, slightly higher than 55.5% found by domestic researchers, and the incidence of anxiety symptoms is 67.25%, higher than 51.0% found abroad [ 6 8 ]. Therefore, psychological intervention for uremic hemodialysis patients is of great significance to the therapeutic effect of patients.…”
Section: Introductionmentioning
confidence: 61%
“…If we cannot get timely and effective counseling and nursing intervention, the continuous bad psychological state is easy to develop into anxiety disorder and depression, which will have a negative impact on the quality of life of patients. Studies have shown that the incidence of depressive symptoms in uremic patients is 68.8%, which is basically the same as 68.0% found abroad, slightly higher than 55.5% found by domestic researchers, and the incidence of anxiety symptoms is 67.25%, higher than 51.0% found abroad [ 6 8 ]. Therefore, psychological intervention for uremic hemodialysis patients is of great significance to the therapeutic effect of patients.…”
Section: Introductionmentioning
confidence: 61%
“…RBC Ca 2+ and ROS may promote the inhibition of flippase and the activation of floppase and scramblase, leading to translocation of PS to the outer membrane leaflet of RBCs [ 18 ]. In vitro studies have shown an increase in PS exposure after a 24 h incubation of RBCs in a severe hypoxic environment (FiO 2 = 5%) [ 31 , 32 ]. Since hypoxic stress was significantly lower in our study, the effects of exercise may have outweighed those of hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In nonacclimatized to altitude athletes, performing a maximal and/or a submaximal exercise in hypoxia results in a greater increase in blood lactate concentration compared to the same exercise performed at sea level [ 28 , 29 ]. In vitro hypoxic studies on RBC reported a decrease in RBC deformability (FiO 2 = 0%, time of exposure: 60 min) [ 30 ] and a rise in PS externalization (FiO 2 = 5%, time of exposure: 24 h) [ 31 , 32 ] after a severe hypoxic exposure. One could, thus, expect greater changes in RBC rheology and senescence markers in athletes exercising in hypoxia compared to normoxic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 We previously showed that hypoxia induces ROS production and eryptosis in healthy RBC. 9,10 In the present study, we explore additional redox pathways that might be altered by hypoxia and uremic toxicity through enzymatic mechanisms such as xanthine oxidase (XO), elevated in the plasma of CKD patients 11 ; superoxide dismutase (SOD), that produces hydrogen peroxide, further converted to water by catalase and glutathione peroxidase 12 ; and heme oxygenase-1 (HO-1), induced by stress, catalyzes free heme degradation, releasing iron, CO, and bilirubin, products with antioxidant, anti-inflammatory, and antiapoptotic effects. 13 Besides the enzymatic defense, plasma and cells contain high levels of reduced glutathione (GSH) to protect cellular components from damage caused by ROS.…”
mentioning
confidence: 99%